Micelle and Surface Tension of Double-Chain Cationic Surfactants - Phan, Chi Minh (ACS Omega, 2018)
[Image: see text] Since the early 20th century, the slightly disparate measurements of a surfactant’s critical micelle concentration, via either surface tension or electrical conductivity, have been assumed one and the same. As a consequence, the possibility that micelles can adsorb at the air/water surface has been disregarded and has led to some abnormalities in the literature that remain as yet unresolved. In this paper, we closely examined the two critical concentrations for a double-chain cationic surfactant. We confirmed that the two concentrations represent two different physical phenomena. Furthermore, the results verified the existence of surface micelles, which are different from the bulk micelles. The formation of the surface micelles can be explained by the structural changes of the adsorption layer, which was also corroborated by molecular simulations. The findings open new challenges to examine the surface adsorption, which  offers new insights into the molecular levels.